Rheumatic Heart Disease-Attributable Mortality at Ages 5-69 Years in Fiji: A Five-Year, National, Population-Based Record-Linkage Cohort Study. - Tom Parks; Joseph Kado; Anne E Miller; Brenton Ward; Rachel Heenan; Samantha M Colquhoun; Till W Bärnighausen; Mariana Mirabel; David E Bloom; Robin L Bailey; Isimeli N Tukana; Andrew C Steer (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Rheumatic heart disease (RHD) is considered a major public health problem in developing countries, although scarce data are available to substantiate this. Here we quantify mortality from RHD in Fiji during 2008-2012 in people aged 5-69 years. METHODS AND FINDINGS:Using 1,773,999 records derived from multiple sources of routine clinical and administrative data, we used probabilistic record-linkage to define a cohort of 2,619 persons diagnosed with RHD, observed for all-cause mortality over 11,538 person-years. Using relative survival methods, we estimated there were 378 RHD-attributable deaths, almost half of which occurred before age 40 years. Using census data as the denominator, we calculated there were 9.9 deaths (95% CI 9.8-10.0) and 331 years of life-lost (YLL, 95% CI 330.4-331.5) due to RHD per 100,000 person-years, standardised to the portion of the WHO World Standard Population aged 0-69 years. Valuing life using Fiji's per-capita gross domestic product, we estimated these deaths cost United States Dollar $6,077,431 annually. Compared to vital registration data for 2011-2012, we calculated there were 1.6-times more RHD-attributable deaths than the number reported, and found our estimate of RHD mortality exceeded all but the five leading reported causes of premature death, based on collapsed underlying cause-of-death diagnoses. CONCLUSIONS:Rheumatic heart disease is a leading cause of premature death as well as an important economic burden in this setting. Age-standardised death rates are more than twice those reported in current global estimates. Linkage of routine data provides an efficient tool to better define the epidemiology of neglected diseases.